Empirical Evaluation of Energy-assisted Protocols for Wireless Sensor Networks - Qureshi, Kalim Uddin; Almutairi, Hanan S R (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
Wireless sensor networks (WSNs) have emerged as a transformative technology with widespread applications in various fields, such as environmental monitoring, healthcare, and industrial automation. This investigation provides a comprehensive evaluation and comparison of an existing protocol, the Energy-Efficient Backbone-assisted protocol for Load Balancing (EBLBP), against two established protocols: Ad-hoc On-Demand Distance Vector (AODV) and Destination Sequenced Distance Vector (DSDV). Through extensive simulations, we analyzed the performance of these protocols across four critical metrics: scalability, efficiency, network lifetime, and energy consumption. Our findings reveal the inherent strengths and weaknesses of EBLBP, AODV, and DSDV, offering insights into their suitability for various WSN deployment scales and conditions. In the simulation environment, EBLBP achieved an impressive 66.67% reduction in overall energy consumption of 100 to 600 node positions, which underlined its positive impact on energy efficiency. The NS2 simulator was used for this investigation. The measured results validate the advantages of EBLBP in terms of energy optimization.